2014
DOI: 10.1371/journal.pone.0109417
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Hill Seeding Density for High-Yielding Hybrid Rice in a Single Rice Cropping System in South China

Abstract: Mechanical hill direct seeding of hybrid rice could be the way to solve the problems of high seeding rates and uneven plant establishment now faced in direct seeded rice; however, it is not clear what the optimum hill seeding density should be for high-yielding hybrid rice in the single-season rice production system. Experiments were conducted in 2010 and 2011 to determine the effects of hill seeding density (25 cm×15 cm, 25 cm×17 cm, 25 cm×19 cm, 25 cm×21 cm, and 25 cm×23 cm; three to five seeds per hill) on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 27 publications
0
28
0
1
Order By: Relevance
“…Phosphorus at 60 kg P 2 O 5 ha −1 in the form of calcium superphosphate was applied as basal. The field management was performed as described by Wang et al (2014) with slight modification. Field trials were conducted in Hangzhou (HZ) (119°54′ E, 30°04′ N) from May to October 2012.…”
Section: Methodsmentioning
confidence: 99%
“…Phosphorus at 60 kg P 2 O 5 ha −1 in the form of calcium superphosphate was applied as basal. The field management was performed as described by Wang et al (2014) with slight modification. Field trials were conducted in Hangzhou (HZ) (119°54′ E, 30°04′ N) from May to October 2012.…”
Section: Methodsmentioning
confidence: 99%
“…Firstly, rice was planted at a proper high density (90–100 plants/m 2 ). Seeding density is an important factor for rice yield ( Lin et al 2011 , Wang et al 2014 ). In our experience, high density seedlings can also promote rice maturation: growing rice seedlings at a proper high density always leads to the mimicking of a short-day effect, and direct planting associated with rational close planting can promote rice to flower earlier by 10–15 days than transplanting rice.…”
Section: Methodsmentioning
confidence: 99%
“…In the study of interspecific hybrids, high-parent heterosis for GNP (8.53%) and KGW (10.47%) resulted in a positive mean of panicle yield heterobeltiosis (3.08%), despite the existence of sterile hybrids (Wang et al, 2014). In another study, the three-line super hybrid rice WFYT025 and its parents showed that high-parent heterosis for yield per plant remained highly significant (22.99%) with p < .01 (Chen et al, 2018).…”
Section: F I G U R Ementioning
confidence: 96%